Revealing the Progenitor of SN 2021zby through Analysis of the TESS Shock-cooling Light Curve - Qinan Wang; Patrick Armstrong; Yossef Zenati; Ryan Ridden-Harper; Armin Rest; Iair Arcavi; Charles D. Kilpatrick; Ryan J. Foley; Brad E. Tucker; Chris Lidman; Thomas L. Killestein; Melissa Shahbandeh; et al. (The Astrophysical Journal Letters, 2023)
We present early observations and analysis of the double-peaked Type IIb supernova (SN IIb) SN 2021zby. TESS captured the prominent early shock-cooling peak of SN 2021zby within the first ∼10 days after explosion with a 30 minute cadence. We present optical and near-infrared spectral series of SN 2021zby, including three spectra during the shock-cooling phase. Using a multiband model fit, we find that the inferred properties of its progenitor are consistent with a red supergiant or yellow supergiant, with an envelope mass of ∼0.30–0.65 M _⊙ and an envelope radius of ∼120–300 R _⊙ . These inferred progenitor properties are similar to those of other SNe IIb with a double-peaked feature, such as SNe 1993J, 2011dh, 2016gkg, and 2017jgh. This study further validates the importance of the high cadence and early coverage in resolving the shape of the shock-cooling light curve, while the multiband observations, particularly UV, are also necessary to fully constrain the progenitor properties.